Plant Uses and Conservation in the Culture of East Sumba - Eka Sulistiyowati; Siti Aisah; Dony Eko Saputro; Nurdin Setio Budi (Journal of Tropical Ethnobiology, 2021)
This study mainly explored plants uses among East Sumba People and how they relate to conservation efforts, especially in several villages, including Lambanapu Village, Kampung Adat Wunga, Prailiu, and Praiyawang. The methods used in this study were combinations of field data collections, interviews, and observations. The findings showed that the traditional uses of plants fall into five use-categories: plants for weaving tenun ikat, building traditional houses, food sources, medicines, and rituals. Local people performed conservation efforts by planting the necessary plants in their garden, protecting local forests, and only using plants/trees which are ready to be harvested. In some occasions, rituals were also performed before harvesting the plants. The traditions showed that Sumba people respect the supernatural beings and the harmony between nature and human.